Age- and Sex-Specific Standard Scores for the Reading the Mind in the Eyes Test - Kynast, Jana; Polyakova, Maryna; Quinque, Eva Maria; Hinz, Andreas; Villringer, Arno; Schroeter, Matthias L. (Frontiers in Aging Neuroscience, 2021)
The reliable, valid and economic assessment of social cognition is more relevant than ever in the field of clinical psychology. Theory of Mind is one of the most important socio-cognitive abilities but standardized assessment instruments for adults are rare. The Reading the Mind in the Eyes Test (RMET) is well-established and captures the ability to identify mental states from gaze. Here, we computed standard scores for the German version of the RMET derived from a large, community-dwelling sample of healthy adults (20-79 years). The standardization sample contains 966 healthy adult individuals of the population-based Leipzig Research Centre for Civilization Diseases (LIFE) study. Before standardization, weighting factors were applied to match the current sample with distribution characteristics of the German population regarding age, sex, and education. RMET scores were translated into percentage ranks for men and women of five age groups (20-29, 30-39, 40-49, 50-59, 60+ years). Age-specific percentage ranks are provided for men and women. Independent of age, men present a larger variance in test scores compared to women. Within the specific age groups, women score higher and their scoring range is less variable. With increasing age, the scoring variance increases in both men and women. This is the first study providing age- and sex-specific RMET standard scores. Data was weighted to match German population characteristics, enabling the application of standard scores across German-speaking areas. Our results contribute to the standardized assessment of socio-cognitive abilities in clinical diagnostics.